Compliance with the Implementation of Health Protocols During the COVID-19 Pandemic for Employees in Hospitals - Gita Fajrianti; Dhesi Ari Astuti; Destu Satya Widyaningsih (The Indonesian Institute of Science and Technology Research, 2023)
RSUD Depati Hamzah (hospital) is a referral hospital for COVID-19 patients. Efforts need to be carried out to prevent and control COVID-19 for employees because it is categorized as a workplace with a high risk of exposure or high potential for close contact with people or patients who are known or suspected to be infected with COVID-19. Non-compliance with implementing health protocols can potentially expand the spread of COVID-19. The purpose of the research is to determine employees' compliance with the implementation of health protocols during the COVID-19 pandemic at RSUD Depati Hamzah. This research is analytical with a quantitative approach with a cross-sectional design. This study's population was all RSUD Depati Hamzah members, and the sample number was 94 respondents. Hospitals need to increase socialization about the impact of COVID-19 disease. It should provide complete facilities and infrastructure in all parts of the work that support the implementation of employee compliance in preventing the transmission of COVID-19, such as symbols or signs of social distancing, posters to provide education and remind employees and visitors of hospital junk about COVID-19.